2011
DOI: 10.1589/jpts.23.391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gong's Mobilization Applied to Shoulder Joint on Shoulder Abduction

Abstract: Abstract.[Purpose] The purpose of this study was to verify the effects of Gong's Mobilization on shoulder abduction range of motion (ROM). [Subjects] In this study, 57 male and female adults whose shoulder abduction ROM was limited to 120 degree or less were selected and separated into a Gong's Mobilization group (n=28) and anterior to posterior gliding group (n=29).[Methods] Gong's Mobilization and an anterior to posterior gliding were repeated 10-15 times. A goniometer was used to measure the shoulder abduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Moreover, contracture of the shoulder posterior capsule is known to cause internal rotation reduction in abduction at 90° 31 ) . Gong et al 32 ) observed that posterior translation is effective for increasing shoulder internal rotation in normal individuals. Thus, the posterior translation applied in the present study likely contributed to the increased internal rotation by stretching the posterior capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contracture of the shoulder posterior capsule is known to cause internal rotation reduction in abduction at 90° 31 ) . Gong et al 32 ) observed that posterior translation is effective for increasing shoulder internal rotation in normal individuals. Thus, the posterior translation applied in the present study likely contributed to the increased internal rotation by stretching the posterior capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of shoulder abduction was performed with the subjects standing against a flat wall and maintaining extension of the elbow joint while restricting lateral flexion of the trunk. The subjects then conducted shoulder abduction and ROM was measured using a goniometer (USA) while the ulnar side of the forearm and the 5th finger remained in contact with the wall 10) . Internal and external rotation of the shoulder were measured with the subject in the supine position, with the GHJ at 90° abduction and the elbow joint (EJ) at 90° flexion, while the front shoulder joint was held to prevent compensatory action, and the rotational axis was fixed to prevent movement during rotation.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results of a previous study, Gong's mobilization was more effective than anterior to posterior gliding at improving shoulder abduction ROM 4) . However, its effectiveness was limited because the mobilization was applied to subjects in the sitting position, and this posture is inappropriate for utilizing gravity and applying acceleration at the same time.…”
Section: Introductionmentioning
confidence: 96%